Subsegmental Pulmonary Embolism - Baumgartner, Christine; Tritschler, Tobias; Aujesky, Drahomir (Hämostaseologie, 2023)
Subsegmental pulmonary embolism (SSPE) is increasingly diagnosed with the growing use and technological advancements of multidetector computed tomography pulmonary angiography. Its diagnosis is challenging, and some presumed SSPE may actually represent imaging artifacts. Indirect evidence and results from small observational studies suggest that SSPE may be more benign than more proximal pulmonary embolism, and may thus not always require treatment. Therefore, guidelines suggest to consider a management strategy without anticoagulation in selected patients with SSPE at low risk of recurrent venous thromboembolism (VTE), in whom proximal deep vein thrombosis is excluded. Recently, a large prospective study among low-risk patients with SSPE who were left untreated showed a higher VTE recurrence risk than initially deemed acceptable by the investigators, and thus was prematurely interrupted after recruitment of 97% of the target population. However, the risk–benefit ratio of anticoagulation for low-risk patients with SSPE remains unclear, and results from randomized trials are needed to answer the question about their optimal management.
Keywords: pulmonary embolism; subsegmental pulmonary embolism; overdiagnosis; overtreatment; anticoagulation